Operationalising and evaluating redundancy and flexibility-based management strategies within a queuing system. Issue 13 (2019) - Mackay, Jonathon; Munoz, Albert; Pepper, Matthew; Ryan, Emily
Abstract: Open systems operating close to maximum capacity are prone to work accumulations when either resources become fatigued and unexpected demand surges occur. As such, decision makers are required to make strategic choices about adjustments to available resources to avoid drift towards entropy and failure. Such work accumulations can continually increase while resource utilisation is maximized, popular risk strategies be applied to assist resilience or robustness. Decision-makers often make choices to implement either flexibility or redundancy strategies, yet little guidance exists as to the relative utilities of each strategy. Adopting a system dynamics (SD) methodology, and a discrete event simulation, this paper evaluates the utility difference between two strategies within a queueing system subject to unexpected demand surges while operating at near maximum capacity. Utilising worker fatigue (as a function of utilisation) as a feedback mechanism influencing capacity, the resultant model suggests non-linearity caused by fatigue influences the utility of redundancy and strategy. The utility is further influenced by the degree of slack built into the system to cope with demand surges. The research offers unique interpretations of the redundancy-flexibility debate and demonstrates the value of a combined SD and discrete event simulation methodology towards determining differences in strategy utilities.